Social enterprises and the privatization of a new model in basic education: A study of public-private relationships in cities of Minas Gerais-Brazil - André Silva Martins; Camila Azevedo Souza; Leonardo Docena Pina (Arizona State University, 2020)
The text presents the result of research on public-private partnerships in Brazil's basic education. We analyzed the relation between the Municipal Executive Power and private organizations in the provision of public education in cities of Minas Gerais. We investigated center cities in the state's mesoregions: Uberlândia, Governador Valadares, Juiz de Fora, and São João Del-Rei. We adopted as an epistemic basis the historical-dialectical materialism and documentary analysis as the methodology. We compiled an empirical corpus with documents from the state apparatus and civil society organizations hired by public entities. We noticed childhood education is the stage in which the new type of privatization process is most advanced. Only one city presented a privatization initiative of a new type in elementary education. We identified: (i) public-private relations are privatization expression of a new type of education; ii) management mechanisms follow the management public administration precepts; (iii) organizations hired by the public power were re-functionalized by management precepts as social companies. We conclude the new public-private relation redefines the idea of public space, destabilizes the democratic management, updates the labor division in education between the public sector and private organizations, and weakens the right to public education.